A Process Development Project For A Case Company - Xu, Junjie (My University, 2023)
This paper presents a case study on a process improvement project undertaken by a company in the sustainable energy industry. The project aimed to optimize the gate model for new product development, implement a hybrid-gate model, develop a gate checklist, and create an R&D process flow chart to better manage the R&D process. The study began with a thorough analysis of the existing gate model, which revealed several bottlenecks and inefficiencies. These were addressed through a series of process improvements, including better definition of gate criteria, improved cross-functional collaboration, and enhanced communication with stakeholders. To further improve the R&D process, the company implemented a hybrid-gate model, which integrated elements of both the stage-gate and agile development methodologies. This approach enabled the company to be more responsive to changes in the market and customer needs while maintaining the discipline and rigor of the stage-gate model. In addition, the project team developed a gate checklist, which provided a standardized set of criteria to evaluate project progress at each gate. This allowed the team to identify and address potential issues early in the development process. To provide greater visibility and understanding of the R&D process, the team also created an R&D process flow chart, which outlined the steps involved in new product development and the flow of information and decision-making. The project was successful in improving the efficiency and effectiveness of the R&D process, resulting in faster time-to-market for new products and increased customer satisfaction. The gate checklist and R&D process flow chart provided greater transparency and accountability, helping to ensure that projects were delivered on time and within budget. Overall, this case study demonstrates the importance of continuous process improvement in the sustainable energy industry and highlights the potential benefits of a hybrid-gate model, gate checklist, and R&D process flow chart for managing complex development projects.
Keywords: fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master's Programme in Industrial Management